Cigarette-Smoke-Induced Dysregulation of MicroRNA Expression and Its Role in Lung Carcinogenesis - Rebecca Russ; Frank J. Slack (Pulmonary Medicine)
Dysregulation of microRNAs (miRNAs), particularly their downregulation, has been widely shown to be associated with the development of lung cancer. Downregulation of miRNAs leads to the overactivation of their oncogene targets, while upregulation of some miRNAs leads to inhibition of important tumor suppressors. Research has implicated cigarette smoke in miRNA dysregulation, leading to carcinogenesis. Cigarette smoke may lead to genetic or epigenetic damage to miRNAs, many of which map to fragile sites and some of which contain single nucleotide polymorphisms. Cigarette smoke may also cause dysregulation by affecting regulatory mechanisms controlling miRNA expression. Researchers have shown a correlation between smoke-exposure-induced dysregulation of miRNAs and age. Furthermore, dysregulation seems to be associated with intensity and duration of smoke exposure and duration of cessation. Longer exposure at a threshold level is needed for irreversibility of changes in expression. Better understanding of miRNA dysregulation may allow for improved biomonitoring and treatment regimens for lung cancer.